The eighth moment of Dirichlet L-functions II - Chandee, Vorrapan; Li, Xiannan; Matomäki, Kaisa; Radziwiłł, Maksym (Duke University Press, 2026)
Abstract
We prove an asymptotic formula for the eighth moment of Dirichlet L-functions averaged over primitive characters χ modulo q, over all moduli q≤Qq≤Q, and with a short average on the critical line. Previously the same result was shown conditionally on the generalized Riemann hypothesis by the first two authors.